THE STUDY OF INHIBITION ABILITY OF MIXED INHIBITOR SODIUM METAVANADATE AND 2-MERKAPTOBENZOTHIAZOLE SODIUM SALT ON CARBON STEEL CORROSION IN A CO2 SATURATED 1% NACL SOLUTION - DIANA MEISYAFITRI HASIBUAN (NIM : 10508104); Pembimbing : Dr. Bunbun Bundjali
Corrosion is the decline in the quality of metal resulting from its chemistry or electrochemistry with his environment. This experiment was focused on research of the efficiency inhibition of mixed inhibitors of sodium metavanadate and 2-merkaptobenzothiazole sodium salt on carbon steel corrosion in CO2 saturated 1% NaCl solution. The specimen of vanadium is very complicated and important for the effectiveness of the obstacle or the control of the rate of corrosion. The solution of metavanadate contained monovanadate that hindered the rate of corrosion strongly from the reduction reaction in oxygen to the same level as chromate. The determination of the rate of corrosion and the inhibition power of inhibitor in this system was carried out with the mass reduction method (wheeltest), and the electrochemistry method, which is: Electrochemical Impedance Spectroscopy (EIS) and the Tafel Extrapolation. The inhibition efficiency of 150 ppm sodium metavanadate in NaCl 1% solution concentrated in the temperature 30 OC was 33.12%. Whereas 15 ppm 2-merkaptobenzothiazole sodium salt in this temperature had inhibition efficiency of 59.53%. The efficiency inhibition of mixed inhibitor sodium metavanadate and 2-merkaptobenzothiazole sodium salt showed a better inhibition efficiency, reaching 63.83% in this temperature by using the method of EIS. Sodium metavanadate has low inhibition efficiency for carbon steel in acid media and the addition of 2-merkaptobenzothiazole sodium salt can increase the inhibition efficiency of sodium metavanadate not only at low temperature but also at high temeperature.